A C5N2 Nanoparticle Based Direct Nucleus Delivery Platform for Synergistic Cancer Therapy. (1st April 2019) - Chen, Weihua; Liu, Jianhua; Wang, Ying; Jiang, Chunhuan; Yu, Bin; Sun, Zhen; Lu, Lehui
Abstract: Intracellular targeting has the same potential as tissue targeting to increase therapy efficacy, especially for drugs that are toxic to DNA. By adjusting intracellular traffic, we developed a novel direct‐nucleus‐delivery platform based on C5 N2 nanoparticles (NPs). Supramolecular interactions of C5 N2 NPs with the cell membrane enhanced cell uptake; abundant edge amino groups promoted fast and effective rupture of early endosomes; and the appropriate size of the NPs was also crucial for size‐dependent nuclear entry. As a proof of concept, the platform was not only suitable for the effective delivery of molecular drugs/dyes (doxorubicin, hydroxycamptothecine, and propidium iodide) and MnO2 nanoparticles to the nucleus, but was also photoresponsive for nucleus‐targeting photothermal therapy (PTT) and photodynamic therapy (PDT) to further greatly increase anticancer efficacy. This strategy might open the door to a new generation of nuclear‐targeted enhanced anticancer therapy. Abstract : Drei Strikes und du bist raus : Eine allgemeine nicht‐peptidische C5 N2 ‐Nanopartikel‐basierte Plattform für die Abgabe von Molekülen und Nanomaterialien an den Zellkern wurde durch Anpassung des intrazellulären Transports entwickelt (siehe Bild). Aufgrund der photoresponsiven Natur der C5 N2 ‐NPs und ihrer Fähigkeit, in den Zellkern einzudringen, war eine verbesserte Chemotherapie, Photothermaltherapie und photodynamische Therapie gleichzeitig möglich.